Analysis of job satisfaction in canyoning and mid-mountain sports technicians - Rojo-Ramos, Jorge; Mogo´´llón-Espinosa, Laura; Gomez-Paniagua, Santiago; Galán Arroyo, Carmen (Revista Iberoamericana de Ciencias de la Actividad Física y el Deporte, 2025)
Job satisfaction is an emotional state that identifies the subjective perception with their experiences and expectations at work. This can affect the quality of the service offered. In order to know the job satisfaction of sports technicians specialized in canyoning and mid-mountain, the job satisfaction scale for sports technicians developed by Sánchez Alcazar Martínez and Parra Meroño was applied to a sample of 114 employees. The results obtained coincide with those observed by other authors, where the most highly valued dimensions are “safety” and “promotion”, with “remuneration” obtaining the lowest values. In addition, “age” and “experience” have been identified as variables that influence some of the areas. It would be important to extend the study and address the variables that influence the job satisfaction of specialized canyoning sports technicians, in order not only to increase their quality of life, but also to improve the quality of the service provided.